Pengaruh Live Streaming Shopping dan E-WOM terhadap Perilaku Impulsive Buying Konsumen Online Akun TikTok @jiniso.id - Syachwaldan Rizky Fadillah Vidayat; Mochammad Arkansyah (Persatuan Wartawan Indonesia, 2023)
The convenience offered in online transactions has triggered an excess of consumers' desire to shop, thereby encouraging the tendency for impulsive buying behavior, especially as a result of sales promotions through live streaming shopping and E-WOM communications. This study aims to find out how live streaming shopping and E-WOM influence the impulsive buying behavior of online consumers using the study of the S-O-R theory. This type of research is explanatory research with quantitative research methods. The population in this study is all followers of the TikTok account @jiniso.id. The sampling procedure used is non-probability with purposive sampling technique. Followers who have purchased Jiniso products during live streaming shopping are the criteria for respondents in this study. The results of research conducted on 100 respondents proved that the two independent variables, namely live streaming shopping and E-WOM, have a joint influence on online consumers' impulsive buying behavior on the TikTok account @jiniso.id.